Low-carbon ammonia-based fuel for maritime transport - A.A. Levikhin; A.A. Boryaev (Results in Engineering)
The review examines decarbonized ammonia as a promising fuel for marine transportation. When ammonia burns, it does not produce carbon dioxide and its energy density is 23 MJ/kg. Liquid ammonia has a volumetric energy density of 15,600 MJ/m3. There are infrastructures for the transmission, storage and distribution of ammonia, since ammonia is one of the main products of chemical production. However, wider use of ammonia as a fuel will require additional investment in specialized infrastructure. Ammonia can be used in internal combustion engines both in pure form and as a mixture with hydrocarbon fuel (dual-fuel engines) and additives that ensure its ignition in existing propulsion systems (hydrogen, acetylene, etc.). The article presents the current list of standards and rules for the use of ammonia. In assessing the potential of using ammonia as a marine fuel, a list of further measures for its implementation is given, including the features of creating engines on ammonia and upgrading existing propulsion systems for using ammonia. Requirements for storage tanks for liquid ammonia and its fire-explosive and toxic properties are also given. Calculated equilibrium values ​​of the energy characteristics of fuels based on liquid ammonia are presented, as well as the results of calculations when using ammonia as a working fluid for electric heating and nuclear rocket engines. The physicochemical properties and thermodynamic characteristics of liquid ammonia, depending on temperature, presented in the article allow developing technologies for its effective and safe use and can be used as reference material.